(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The main purposes of this study are to explore the extent to which public Jordanian universities have adopted Human Resource Information System (HR PLANNING) and to examine the current HR PLANNING uses, benefits and barriers in these universities. A structured questionnaire was constructed based on other previous studies, it also pre-tested, modified and translated to capture data from HR PLANNING users in Jordanian universities. The main findings of this study reveled that the quick response and access to information were the main benefits of HR PLANNING implementation. While, the insufficient financial support; difficulty in changing the organization’s culture and lack of commitment from top managers were the main HR PLANNING implementation barriers. The present study provides some insights into the performance and applications of HR PLANNING in Jordanian universities that could help Human Resource Management (HRM) practitioners to get a better understanding of the current HR PLANNING uses, benefits and problems, which in turn, will improve the effectiveness of HR PLANNING Scholars in many disciplines have considered the antecedents and consequences of various forms of trust. This paper generates 11 propositions exploring the relationship between Human Resource Information Systems (HR PLANNING) and the trust an individual places in the inanimate technology (technology trust) and models the effect of those relationships on HR PLANNING implementation success. Specifically, organizational, technological, and user factors are considered and modeled to generate a set of testable propositions that can subsequently be investigated in various organizational settings. Eleven propositions are offered suggesting that organizational trust, pooled interdependence, organizational community, organizational culture, technology adoption, technology utility, technology usability, socialization, sensitivity to privacy, and predisposition to trust influence an individual’s level of trust in the HR PLANNING technology (technology trust) and ultimately the success of an HR PLANNING implementation process. A summary of the relationships between the key constructs in the model and recommendations for future research are provided.